[Macleod (Colonial Secretary) on Africa, 29th December 1959] - Great Britain Colonial Office; Macleod, Iain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1959)
Report to the Prime Minister by the Secretary of State, Iain Macleod, following his Dec. 1959 visit to Malta and East Africa